Inter-temporal savings, current account dynamics and asymmetric shocks in a heterogeneous European Monetary Union - Gunther Schnabl; Holger Zemanek (Center for Economic Studies and ifo Institute (CESifo), 2010)
In the current debate on the reasons and implications of the Greek and Irish euro crisis, the intra-European current account imbalances have gained rising attention. Whereas Greece and Ireland struggle for austerity in private and public spending, Germany is urged to reduce its current account surplus by increasing wages to forestall a new build-up of unsustainable intra-E(M)U indebtedness. We analyse the emergence of intra-European imbalances since the year 1990 based on the theory of optimum currency areas. We show that the asymmetric shock of the German unification can be seen not only as the origin of the 1992/93 crisis of the European Monetary System, but also for the rising intra-European current account imbalances since the euro introduction and thereby the current European debt crisis. Based on this finding we argue that an increase of German spending to reduce its current account surplus is not only in the interest of German taxpayers to contain financial risk, but would also impose austerity on the rest of Europe. The resulting new wave of crisis could trigger a new round of monetary expansion in the EMU.
Keywords: E21; F15; F32; F36; 330; monetary union; German unification; asymmetric shock; current account imbalances; inter-temporal savings; financial crisis; euro crisis; European debt crisis; theory of optimum currency areas; Europäische Wirtschafts- und Währungsunion; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Optimaler Währungsraum; Zeitpräferenz; Währungskrise; Finanzmarktkrise; EU-Staaten; Nationale Einheit; Schock; Deutschland